2009
DOI: 10.1002/elan.200904646
|View full text |Cite
|
Sign up to set email alerts
|

Ex situ Voltammetry and Chronopotentiometry of Doxorubicin at a Pyrolytic Graphite Electrode: Redox and Catalytic Properties and Analytical Applications

Abstract: Ex situ (adsorptive transfer stripping) electrochemical techniques in connection with basal-plane PGE have been applied to the study of redox and catalytic properties of doxorubicin (DOX). Cyclic and square-wave voltammetry and constant current chronopotentiometric stripping (CPS) analysis were used to follow reversible reduction of DOX quinone moiety around À 0.5 V and its coupling to catalytic oxygen reduction. CPS was for the first time used for sensitive ex situ determination of the DOX using the catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…In agreement with data published in 10a, peak O cat height was strongly depressed in the presence of an excess of dsDNA, interacting with DOX to form intercalative complexes (Fig. 3 C).…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with data published in 10a, peak O cat height was strongly depressed in the presence of an excess of dsDNA, interacting with DOX to form intercalative complexes (Fig. 3 C).…”
Section: Methodssupporting
confidence: 92%
“…DOX is an antitumor anthracycline antibiotic binding to dsDNA in the intercalative mode, exhibiting well pronounced electrochemistry due to two quinone/hydroquinone redox pairs with redox potentials around +0.5 V (corresponding to a SWV peak denominated here as DOX red , well separated from the peak WLA q red due to WLA see Figure 3 B) and around −0.5 V. The latter redox process is coupled with catalytic reduction of oxygen to hydrogen peroxide, under aerobic conditions giving rise to the peak O cat (Figure 3 B) that was previously used 10a for monitoring of DOX‐dsDNA interactions. Here we used the peak O cat , together with simultaneously measured peak WLA red (using SWV procedure optimized in 10a; these measurements were performed on air. Considerably smaller WLA peak currents, compared to other measurements in this paper, are caused by 10‐fold lower SWV frequency applied in this experiment) for evaluation of competitive binding of WLA and DOX to dsDNA.…”
Section: Methodsmentioning
confidence: 88%
“…The same catalytic oxygen reduction of doxorubicin was obtained at a pyrolytic graphite electrode. It was observed that the reduction of oxygen at a bare electrode in electrolyte solution (without Dox) occurs at a potential around À1.0 V [41], while in the presence of Dox, the potential of the oxygen reduction was at À0.5 V [42]. Baring this in mind, a study of the doxorubicin interaction with the GSH modified electrodes investigated in the present work was performed and the results are reported in the followings.…”
Section: Interactions Of Au-gsh Ad Surface With Doxorubicinmentioning
confidence: 75%
“…We assume it will be possible to apply the results for study of the interactions of the alkaloids with biopolymers at PGE as we have recently demonstrated in the case of analysis of the interactions of the anti-tumor drug doxorubicin with DNA [28,29]. The results could also contribute to the general theory of the oxidation of isoquinolines and application of the results for sensitive analysis based on adsorptive accumulation on the surface of carbon electrodes.…”
mentioning
confidence: 95%